Hubungan Perilaku Caring Perawat dengan Pelaksanaan Handover Di RSUD Raja Ahmad Tabib Provinsi Kepulauan Riau - Pertiwi, Huilianti; Muharni, Sri; Wardhani, Utari Christya (Universitas Fort De Kock Bukittinggi, 2023)
Background: Conditions that indicate that there are still deficiencies in implementing caring behavior and effective handovers at the Raja Ahmad Tabib Regional Hospital in Riau Islands Province This study aims to identify the relationship between nurses' caring behavior and the implementation of handovers at Raja Ahmad Tabib Hospital, Riau Islands Province. Methods: In this research, researchers used quantitative research methods with a cross-sectional design. The sample consisted of 87 respondents with a sampling technique, namely proportional random sampling. This research used a questionnaire instrument containing 21 questions related to the seven components of caring, according to Rouch, and data analysis used a Likert scale and chi-square test. Results: Univariate analysis showed that nurses' caring behavior was in the good category by as much as 55% and handover implementation was in the correct category by as much as 66%. Bivariate results show that there is a significant relationship between nurses' caring behavior and handover implementation, with a P-value of 0.0003 (<0.05). Conclusion: It was concluded that there was a significant relationship between nurses' caring behavior and the implementation of handovers in the inpatient room. It is recommended that nurses pay attention to and develop caring behaviors in order to increase accuracy in implementing handover activities.Keywords: Caring Behavior, Handover Implementation, Nursing